Pemahaman Masyarakat Dusun Sawit Terhadap Hukum Waris Islam - Rahmatul Khasanah; Besse Elfi Yuwinda; M. Syarifudin ‎; Herdiansyah (Indra Institute Research & Publication, 2023)
Every life in the world will surely end in death. The death of a human being will result in an exchange of property rights from someone who has died (deceased) for his living heirs, an exchange of registered property rights in the form of animate assets or inanimate assets. With this commonly referred to as inheritance. Indonesia is the country with the largest Muslim population in the world. As Muslims, it has become an obligation to be close to Islam by understanding and studying provisions in Islamic law, including the method of inheritance distribution. But do people still understand and use Islamic inheritance laws in dividing their inheritance at this time? The method used by researchers in this study is empirical legal research or legal sociology, which is descriptive qualitative in nature. This research intends to describe or interpret a case seriously and is done by gathering as much information as possible. In writing this article, the writer can conclude that, the people of Dusun Sawit, Suhada Village, Enok District, Indragiri Hilir Regency, it turns out that the majority of the people do not understand Islamic inheritance law.